1990
DOI: 10.1007/bf00003398
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate-2-sulfate as a dietary vitamin C source for atlantic salmon (Salmo salar): 1. Growth, bioactivity, haematology and humoral immune response

Abstract: The present experiment shows that ascorbate-2-sulfate (AS) is not equivalent to ascorbic acid (AA) as a dietary vitamin C source for Atlantic salmon (Salmo salar). Within reasonable feed supplemental levels AS does not provide the tissues with adequate supplies of vitamin C to secure optimal physiological functions as demonstrated by biochemical and haematological analyses.AS could not be detected in the liver of fish fed either AA or AS, nor in vitamin C - deprived salmon, suggesting that AS is not the natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1
4

Year Published

1990
1990
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 28 publications
2
29
1
4
Order By: Relevance
“…Ascorbate has been shown to influence the absorption and utilization of iron in fish (Sandnes et al 1984;Maage et al 1990), and anemia has been reported in AA deficient fish (Hilton 1984;Sandnes et al 1990). The total serum iron concentration was significantly (p < 0.005) correlated to the liver AA concentration in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ascorbate has been shown to influence the absorption and utilization of iron in fish (Sandnes et al 1984;Maage et al 1990), and anemia has been reported in AA deficient fish (Hilton 1984;Sandnes et al 1990). The total serum iron concentration was significantly (p < 0.005) correlated to the liver AA concentration in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…As in landliving animals, vitamin C deficiency has been shown to reduce resistance against infections (Beisel 1982;Durve and Lovell 1982;Li and Lovell 1985;Wahli et al 1986;Navarre and Halver 1989;Anggawati-Satyabudhy et al 1989;Sandnes et al 1990;Hardie et al 1991). Further, immune stimulating effects and increased disease resistance in fish fed high doses of vitamin C have been reported in channel catfish, Ictalurus punctatus (Durve and Lovell 1982;Li and Lovell 1985), rainbow trout, Oncoryhnchus mykiss (Blazer 1982;Wahli et al 1986;Navarre and Halver 1989;Anggawati-Satyabudhy et al 1989;Verlhac et al 1993) and Atlantic salmon, Salmo salar (Hardie et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…A prime function of AA appears to be that of a reducing agent maintaining metaloenzymes in a reduced and active state (Padh 1991). Examples of physiological effects of AA demonstrated in fish are related to reproduction (Sandnes et al 1984;Soliman et al 1986;Waagb0 et al 1989), immune functions and disease resistance (Durve and Lovell 1982;Navarre and Halver 1989;Hardie et al 1991), iron metabolism and hematology (Hilton et al 1978;Maage et al 1990;Sandnes et al 1990), lipid metabolism (John et al 1979;Waagb0 et al 1989), interactions with other micronutrients (Hilton 1989, Maage et al 1990, stress (Wedemeyer 1969), brain neurotransmitters (Johnston et al 1989) and en- (Pang 1971;Thomas and Neff 1984). The AA requirement is thus influenced by many factors, and it is therefore necessary to establish the minimum required dietary level to avoid deficiency symptoms and to support growth under a variety of normal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Ascorbate-2-sulfate (AS) has been suggested as a stable vitamin C source in fish diets (Tucker and Halver 1986) and has been used commercially. Recent studies have shown that the bioactivity of this compound is limited in Atlantic salmon, Salmo salar (Sandnes et al 1990) and in rainbow trout, Oncorhynchus mykiss (Dabrowski and Kock 1989).…”
Section: Introductionmentioning
confidence: 99%
“…A detailed description of the experimental design, antigen injection and antibody detection is given by Sandnes et al (1990). The copper, zinc and cadmium content in each injected dose was 55 ng, 6 ng and < 0.15 ng, respectively.…”
Section: Introductionmentioning
confidence: 99%